The role of fluoroscopy in the removal of tracheobronchial pin aspiration - BATIREL, HASAN FEVZİ (BLACKWELL PUBLISHING, 2006)
In this study, we investigated the role of fluoroscopy in the bronchoscopic removal of aspirated pins. Of 373 patients who underwent bronchoscopy for presumed tracheobronchial foreign body aspiration, 56 pin aspiration cases were selected and divided into two groups according to whether fluoroscopic guidance was required (group I) or not (group II). The localisation of foreign bodies, mortality and morbidity ratios and the duration of the procedures were investigated. Pin aspiration percentage was 15. Pins were mostly located in peripheral airways in group I, and in central airways in group II (p < 0.05). The mean duration of the procedure was 42 +/- 30 min in group I and 17 +/- 13 min in group II (p < 0.01). There was no mortality. Morbidity percentage was 7 in group I and 12 in group II (p > 0.05). No thoracotomy was required in any cases. Fluoroscopic guidance is safe and carries no additional morbidity and mortality and can be used for pins in the tracheobronchial tree.
Keywords: fluoroscopy; foreign body; pin aspiration; bronchoscopy; tracheobronchial tree; FOREIGN-BODY ASPIRATION; LAPAROSCOPIC REMOVAL; BODIES; BRONCHOSCOPY; CHILDREN; NEEDLE; AIRWAY; MANAGEMENT; GUIDANCE